Active Learning:An Instructional Technique for Improving Educational Practices - Sharma, Archana; Arora, Amarpreet Singh (Journal of Engineering Education Transformations, 2019)
Collaborative and Active-learning techniques are known to many faculties but they are reluctant to use them in their classes. One of the foremost reasons for not implementing the instructional techniques is their perception about it that it takes too much time and the course remains uncovered. The instructor cannot cover as much material in the course incorporating active learning techniques. Secondly, an instructor requires a lot of time preparing lectures with active learning techniques. A growing body of evidence suggests that students learn more information when they are asked to engage it actively (Springer, 1998). Some case studies have been presented in support of the active and collaborative learning techniques which the millennial learners prefer and that proved that students learning will be life-long when engaged in learning material. Collaborative and active learning techniques along with lecture were used in two courses to prepare the students for the workplace.